Processional and Chapel Oracular Practice in The Place of Truth - Štub?ová, Silvia.
Standing in stark contrast to the relative wealth of evidence about royal and temple based oracles, there is little to give us some notion of the analogous oracular practices of private religion during the New Kingdom of Egypt. The surviving documentation suggests that private individuals could approach their gods for oracular advice during festival processions. However, based on the Deir el-Medina materials, I argue that in addition to processional oracles, chapel oracles were employed by the villagers as well, if not more largely by common people in ancient Egypt. At Deir el-Medina, the former was given by the patron of the village, the deified king Amenhotep I, and was employed in an official setting in order to solve legal disputes. In contrast, the less documented chapel oracles, which could be perhaps delivered by deities other than Amenhotep I, concerned mostly mundane affairs. In both cases, however, oracles were mediated by the priests servicing the gods. This paper seeks to bring together and examine two sorts of evidence that are usually dealt with separately. Firstly, it provides an analysis of the available written testimonies on oracular ostraca found at Deir el-Medina, and discusses their textual significance by showing who the petitioners were, what kind of questions they asked and what the structure of the questions was. Secondly, it examines the archaeological remains of the chapels connected with oracles at Deir el-Medina and the role of the “brotherhood” of priests associated with them. I conclude with some remarks about the mechanics of the chapel oracles in connection with the modalities of their reception and the status of belief and faith.  doi: http://dx.doi.org/10.5913/jarce.53.2017.a013